46th Winter School on Wave and Quantum Acoustics XLVth Jubilee Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, February 27 –March 2, 2017 - on Acoustic, Winter Schools (Archives of Acoustics, 2017)
46th Winter School on Wave and Quantum Acoustics constitutes a platform for sharing the results and achievements obtained in different branches of physical acoustics. During the Conference Workshop on Acoustoelectronics and Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods will be held. XLVth Jubilee Winter School on Environmental Acoustics and Vibroacoustics is the forum for all environmental and vibroacoustics fields. Particularly it concerns traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems. During the Conference in association with SVANTEK there will be organised seminars on “Measurement of noise and vibration at the workplace”, “Enivironmental noise monitoring” combined with measurement workshops.